Geneza herezji i postawa wobec heretyków na podstawie "Konstytucji apostolskich" - Kieling, Michał (Vox Patrum, 2019)
The basic source of the analysis is the text of The Apostolic Constitutions. The main object of the analysis is for the most part Book 8 entitled: About Schisms and heresis. The Apostolic Constitutions form a compilation of former texts such as: Didaskalia, Didache, Traditio Apostolica. The aim of the study is the presentations of different views on the genesis of heresy and different attitudes towards heretics. The collection consists of eight books and has both a legal and liturgical character. It is also rich in doctrinal (theological) guidance. Moreover, it contains practical guidelines aimed at the clergymen and laity. The Apostolic Constitutions were written in Antakaya about year 380. At that time the city was highly multi-cultural and thrived being a centre of the three cultures: Hellenic, Christan and Jewish. The paper consists of three parts followed by an introduction. In the first part the genesis of heresy in the Old Testament is described. The second part describes the origins of heresy in Christianity. The third part is devoted to practical guidelines relating to the Christians’ attitudes towarda heretics and their relations. The anaysis of the text leads to the conclusion that rejecting the Law and the teaching of prophets and Apostoles as well as orthodox doctrine of Church results in heresy. The Apostolic Constitutions underlile the distinctive authotity of Saint Peter as a bishop of Rome and the preacher of the faith, as well as the apostolic character of the Christian doctrine.